(untitled) (Journal of Libya for geographical studies, 2022)
The old city of Taiz is still home to many religious and archaeological monuments. These landmarks date back to several periods and eras from ancient states that followed the city; nonetheless, despite the presence of this huge number of sites, it suffers from the deterioration of its archaeological identity and lacks an accurate digital database that keeps pace with the requirements of modern times and meets the great and increasing demand for it by tourists and those interested in knowing about its archaeological value, which imposes the need to preserve its heritage through documentation in a way that avoids the shortcomings of the traditional methods used in documentation, through the use of modern technologies. The study aimed and thus concluded in constructing a practical model to apply GIS in terms of managing and documenting archaeological tourism in the old city in order to enlighten decision-makers about the importance of using modern technologies in tackling the issue of archaeological sites’ preservation. In order to achieve the research objectives, a number of approaches were combined, including the system approach and the descriptive analytical approach, in addition to a number of research methods, including photography and cartographic representation using (GIS); moreover, field study was the main tool for data collection to achieve the objectives of the study.